Improving the composition of voluntary programs in the category of Women in fitness - Беленькая, Ирина; Муллагильдина, Алла (Slobozhanskyi Herald of Science and Sport, 2018)
Iryna Bilenka & Alla Mullagildina Purpose: to reveal the basic directions of perfection of construction of compositions of voluntary programs in the category of Women in fitness. Material & Methods: judges-experts analyzed the structure and content of voluntary competitive programs of performances of six female athletes'-finalists of the championship of Ukraine on bodybuilding and fitness in 2016. Results: voluntary programs include elements of structural groups of varying complexity: "acrobatic", "choreographic", "strength" and "flexibility"; female athletes with better indicators in the quantitative analysis of competitive compositions received higher grades for performance; the results of athletes for an arbitrary program are directly proportional to the number of complex elements in the composition. Conclusions: in an voluntary program in women's fitness for a competitive result affects the saturation of the program, the variety and complexity of the elements.